Scaling up and down: movement ecology for microorganisms. Issue 3 (March 2023) - Wisnoski, Nathan I.; Lennon, Jay T.
Abstract: Movement is critical for the fitness of organisms, both large and small. It dictates how individuals acquire resources, evade predators, exchange genetic material, and respond to stressful environments. Movement also influences ecological and evolutionary dynamics at higher organizational levels, such as populations and communities. However, the links between individual motility and the processes that generate and maintain microbial diversity are poorly understood. Movement ecology is a framework linking the physiological and behavioral properties of individuals to movement patterns across scales of space, time, and biological organization. By synthesizing insights from cell biology, ecology, and evolution, we expand theory from movement ecology to predict the causes and consequences of microbial movements. Highlights: Our mechanistic understanding of the machinery that powers microbial motility has advanced considerably alongside mounting evidence from the ecological literature that dispersal plays a key role in structuring patterns of microbial biodiversity. Despite the parallel developments in these fields, they have focused largely on microbial movement at different scales, hindering the cross-scale integration from individual motility behavior to the dynamics of populations and communities. Movement ecology is a recent framework that could provide a means to integrate across these different perspectives to better understand microbial movement and explicitly identify the fundamental features of movement. Empirical studies using novel techniques have revealed important ways that microorganisms can sense and move through different environments, unlocking the potential to study microbial motility at different scales from a movement ecology perspective.